LITERASI KEUANGAN PEDAGANG KAKI LIMA DI AREA KAMPUS UNIVERSITAS SANATA DHARMA MRICAN - Purwanti, Rita Eny (Universitas Sanata Dharma, 2024)
The purpose of this study is to find out whether street vendors in the Sanata Dharma University Mrican campus area have good financial literacy. Financial liquidity is a fundamental thing that affects business continuity for traders. This research uses a qualitative method with a grounded theory approach to find the extent of the financial literacy of traders. The researcher conducted interviews with traders in April 2024 in the Sanata Dharma University Mrican campus area. Traders in determining the selling price of merchandise are not based on the calculation of the basic price, but only follow the price determined by other traders whose merchandise is similar to sell in other locations in the Yogyakarta area. In calculating profit or loss, it is also only based on estimates. Observing these conditions, there is a need for coaching and training for street vendors, especially about financial management and accounting defects in a simple way. With the existence of coaching and training, it is hoped that traders have the competence to carry out financial management, record their economic activities regularly and consistently, so that their trading business is more advanced and can plan to increase their business or innovate by creating new merchandise, so that they are better able to survive. Keywords: Street vendor, financial literacy, coaching and training